Honey bee abundance in pan traps, pooled across the full season per transect, with transects ordered by increasing honey bee abundance, and coloured by distance from nearest bee hives. - Sydney H. Worthy (16541959) (2024)
In the transect names, 100 indicates 100 m, 500 indicates 500 m, and 5000 indicates 5000 m distances from hives. Reprinted from Worthy et al. [29] under a CC BY license, with permission from PLOS ONE, original copyright 2023. (TIF)